Hormonal balance, anovulatory cycles and luteal phase deficiency: exploring relationships between hematological variables, sex hormones and V̇O2max in athletes - Paula Recacha-Ponce; Pilar Suárez-Alcázar; Carlos Hernando; Pablo Salas-Medina; Maria Muriach; Pablo Baliño; Isabel Guisado-Cuadrado; Eladio Collado-Boira (Reproduction and Fertility)
The impact of the menstrual cycle on physical fitness in athletes remains controversial in the scientific literature. Notable fluctuations in sex hormones occur at three key phases of the menstrual cycle, during which estrogen and progesterone levels vary significantly. In addition, the presence of regular bleeding does not ensure ovulation; therefore many women may not be aware that they have anovulatory cycles. These sex hormones can influence the physiology of women and can affect their level of cardiorespiratory performance depending on the phase of the menstrual cycle they are in. Method: Twenty-seven women aged 18–40 years with regular cycles were recruited. All participants had to be athletes classified as level II–III of the McKay et al. 2022 proposal based on training volume/physical activity metrics, among other variables. Cardiorespiratory fitness was indirectly assessed using V̇O2max measurements. Blood samples were collected on three occasions to determine the phase of the menstrual cycle by analyzing sex hormone levels. In addition, urine analyses were performed to detect ovulation, which was positive in all participants. To classify a cycle as ovulatory, progesterone levels must reach 16 nmol/L during the mid-luteal phase. However, it was observed that 26% of the sample did not reach this threshold, exhibiting anovulatory cycles or cycles with deficient luteal phases. Thus, two study groups were created: the ovulatory menstrual cycle group (n = 20) and the menstrual cycle group with deficient/anovulatory luteal phases (n = 7). These groups did not show statistically significant differences in age, weight, body mass index or V̇O2max during the bleeding phase (phase I). Female sex hormones did not show significant differences in the anovulatory cycle group, whereas they did show significant differences in the ovulatory cycle group. A high prevalence of female athletes with anovulatory menstrual cycles was observed. Women with ovulatory cycles experienced changes in their V̇O2max (P = 3.78E−4), in contrast to women with anovulatory cycles, who exhibited stable V̇O2max levels throughout their cycle (P = 0.638). Women with anovulatory menstrual cycles exhibit linear patterns of sex hormones throughout the menstrual cycle, which could lead to the maintenance of physical fitness throughout the cycle. In ovulatory cycles, it would be possible to polarize the training load according to the phase of the menstrual cycle. Monitoring ovulation, in addition to menstrual bleeding, is necessary to enhance knowledge about women’s reproductive health.